2019
DOI: 10.5194/acp-19-3981-2019
|View full text |Cite
|
Sign up to set email alerts
|

The role of chlorine in global tropospheric chemistry

Abstract: Abstract. We present a comprehensive simulation of tropospheric chlorine within the GEOS-Chem global 3-D model of oxidant–aerosol–halogen atmospheric chemistry. The simulation includes explicit accounting of chloride mobilization from sea salt aerosol by acid displacement of HCl and by other heterogeneous processes. Additional small sources of tropospheric chlorine (combustion, organochlorines, transport from stratosphere) are also included. Reactive gas-phase chlorine Cl*, including Cl, ClO, Cl2, BrCl, ICl, H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
358
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 243 publications
(419 citation statements)
references
References 123 publications
21
358
4
Order By: Relevance
“…As noted already, WINTER results showed that the reactive uptake of ClNO 2 on aerosol particles is an important source of Cl 2 during nocturnal periods (Haskins et al, ). When including an advanced representation of tropospheric Cl chemistry into the GEOS‐Chem model, Wang, Jacob, et al () showed that the model could reproduce vertical profiles of HCl from the WINTER campaign, in addition to ClNO 2 being mainly concentrated in the MBL at night. A deficiency was that the model overpredicted Cl 2 at night, which was suggested to be linked to uncertainties in the rate of the heterogeneous reaction between ClNO 2 and Cl ‐ .…”
Section: Synthesis Of Results and Future Outlookmentioning
confidence: 99%
“…As noted already, WINTER results showed that the reactive uptake of ClNO 2 on aerosol particles is an important source of Cl 2 during nocturnal periods (Haskins et al, ). When including an advanced representation of tropospheric Cl chemistry into the GEOS‐Chem model, Wang, Jacob, et al () showed that the model could reproduce vertical profiles of HCl from the WINTER campaign, in addition to ClNO 2 being mainly concentrated in the MBL at night. A deficiency was that the model overpredicted Cl 2 at night, which was suggested to be linked to uncertainties in the rate of the heterogeneous reaction between ClNO 2 and Cl ‐ .…”
Section: Synthesis Of Results and Future Outlookmentioning
confidence: 99%
“…Li et al (2016) implemented the ClNO 2 production in WRF‐Chem and reported a significant increase of O 3 levels (up to 7.23 ppbv or 16.3%) in China. Wang et al (2019) updated the chlorine chemistry in GEOS‐Chem and found neutral to negative effect of chlorine chemistry and natural chlorine sources on O 3 in China. Note that Wang et al (2019) did not include the anthropogenic chlorine in their assessment because the use of a global chlorine emission inventory (RCEI, Keene et al, 1999) overestimated the observed chlorine species on a global scale in their model.…”
Section: Resultsmentioning
confidence: 99%
“…Such enrichment could result, for instance, through GOM transport from the free troposphere via intrusion and boundary layer expansion. These processes may result in Br and Cl enrichment in case that their concentrations are higher in the free troposphere than in the boundary layer, as supported for reactive bromine species (Wang et al 2015, Schmidt et al 2016, Badia et al 2019 and more speculatively for reactive chlorine species (Wilmouth et al 2018, Wang et al 2019.…”
Section: Model Simulations: Remote Marine Boundary Layer Vs a Pollutmentioning
confidence: 92%